Association of Bone Morphogenetic Protein 6 With Exocrine Gland Dysfunction in Patients With Sjögren's Syndrome and in Mice1. Issue 12 (December 2013) - Yin, Hongen; Cabrera‐Perez, Javier; Lai, Zhenan; Michael, Drew; Weller, Melodie; Swaim, William D.; Liu, Xibao; Catalán, Marcelo A.; Rocha, Eduardo M.; Ismail, Nevien; Afione, Sandra; Rana, Noreen A.; et al.
<x xml:space="preserve">Abstract</x> Objective Primary Sjögren's syndrome (SS) is characterized by autoimmune activation and loss of function in secretory epithelia. The present study was undertaken to investigate and characterize changes in the epithelia associated with the loss of gland function in primary SS. Methods To identify changes in epithelial gene expression, custom microarrays were probed with complementary RNA (cRNA) isolated from minor salivary glands (MSGs) of female patients with primary SS who had low focus scores and low salivary flow rates, and the results were compared with those obtained using cRNA from the MSGs of sex‐matched healthy volunteers. The effect of bone morphogenetic protein 6 (BMP‐6) on salivary gland function was tested using adeno‐associated virus–mediated gene transfer to the salivary glands of C57BL/6 mice. Results A significant increase in expression of BMP‐6 was observed in RNA isolated from SS patients compared with healthy volunteers. Overexpression of BMP‐6 locally in the salivary or lacrimal glands of mice resulted in the loss of fluid secretion as well as changes in the connective tissue of the salivary gland. Assessment of the fluid movement in either isolated acinar cells from mice overexpressing BMP‐6 or a human salivary gland cell line cultured with BMP‐6 revealed a loss in volume regulation in these cells. Lymphocytic infiltration in the submandibular gland of BMP‐6 vector–treated mice was increased. No significant changes in the production of proinflammatory cytokines or autoantibodies associated with SS (anti‐Ro/SSA and anti‐La/SSB) were found after BMP‐6 overexpression. Conclusion In addition to identifying BMP‐6 expression in association with xerostomia and xerophthalmia in primary SS, the present results suggest that BMP‐6–induced salivary and lacrimal gland dysfunction in primary SS is independent of the autoantibodies and immune activation associated with the disease.